MicroRNA-146a rs2910164 is associated with severe preeclampsia in Black South African women on HAART. Issue 1 (December 2017) - Maharaj, Niren; Ramkaran, Prithiksha; Pillay, Siddharthiya; Chuturgoon, Anil
Abstract Background South African (SA) Black women have a high prevalence of preeclampsia and HIV, both conditions associated with increased inflammation. miR-146a is an inflammatory-associated miR and a common single nucleotide polymorphism (rs2910164) has been associated with several disease conditions. To date, this SNP has not been investigated in SA Black women. We therefore aimed to investigate the miR-146a G > C SNP in SA Blacks with preeclampsia, and further examine possible association among preeclamptic (PE) women with HIV infection on HAART. Methods This hospital-based, case-control study included 95 normotensive and 98 PE Black SA women (aged 16–46 years old). Patients and controls were genotyped by PCR-RFLP. Using a Cytometric Bead Array assay, serum cytokine levels (including Th1- and Th2-related cytokines) were determined in 4 groups of pregnant women, viz: normotensive, HIV infected, PE + HIV infected, and PE women. Results There was no significant association between the miR-146a polymorphism and PE susceptibility in our data. However, in the subgroup analyses, the variant genotypes (GC/CC) were significantly associated with lower severe PE risk (p  = 0.0497), more especially in the presence of HIV and HAART (p  = 0.017). In the normotensive group, the variant genotypes were associated with lower IL-2 in both the total normotensive group (269 ± 1.26 (36) vs 273 ± 1.31 (23);p  = 0.035) and the PE HIV+ sub-group 265 ± 1.54 (19) vs 271 ± 1.38 (11);p =  0.008). Conclusions Our study suggests that miR-146a rs2910164 polymorphism might not be associated with PE susceptibility, cytokines or related features. However, the miR-146a GC/CC genotype might reduce susceptibility to severe PE, which might be further influenced by the presence of co-morbid HIV infection among pregnant women on HAART. This variant genotype may also be associated with reduced circulating IL-2 levels and thus reduced pro-inflammatory response in normotensive women, which may be further influenced by the presence of HIV infection and HAART.